Complex Analysis for Practical Engineering - Sato, Kozo (Springer International Publishing : Imprint: Springer, 2015)
Maximizing reader insights into the fundamentals of complex analysis, and providing complete instructions on how to construct and use mathematical tools to solve engineering problems in potential theory,  this  book covers complex analysis in the context of  potential flow problems. The basic concepts and  methodologies covered are easily extended to other problems of potential theory. Featuring case studies and problems that aid readers understanding of  the key topics and of  their application  to practical engineering problems, this book is suitable as a guide for engineering practitioners. The complex analysis problems discussed in this book will prove useful in solving practical problems in a variety of engineering disciplines, including flow dynamics, electrostatics, heatconduction and gravity fields.